Maximizing Mandatory Spending in the Education Sector through Collaborative Governance - Fakhruddin Ginta Perdana; Kgs, M. Sobri; Slamet Widodo; Raniasa Putra (Dinasti International Journal of Education Management And Social Science, 2025)
The objective of this research is to explore the management of Mandatory Spending in Ogan Ilir Regency, what challenge it faced, and demonstrate that Collaborative Governance offers a viable solution to the coordination challenges that have historically undermined the effectiveness of mandatory spending in the education sector. This research used descriptive qualitative research method. The study reveals that effective coordination between various governmental and non-governmental stakeholders is crucial for optimizing the use of mandatory spending in education. The allocation of resources, particularly for educational facilities and infrastructure, plays a pivotal role in enhancing the quality of education. However, in Ogan Ilir, issues such as bureaucratic delays, lack of transparency, and inefficient fund management have hampered the effective use of these resources. Despite the challenges, the principles of collaborative governance present a promising solution. By fostering cooperation between local governments, educational institutions, and civil society, the management of mandatory spending can become more transparent and efficient.